PRAKTEK EKSEKUSI ASET PERUSAHAAN DEBITOR PAILIT MENURUT UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (STUDI KASUS PUTUSAN NOMOR 11/PDT.SUS-PAILIT/2017/ PN.NIAGA.SMG) - Chairul Maksus Syam; Stanislaus Atalim (Jurnal Hukum Adigama, 2020)
Bankruptcy occurs not only for small capital companies, companies with big names or brands are not free from the risk of bankruptcy. Even the confiscation of the assets of a bankrupt company has experienced obstacles and the bankruptcy bill is not sufficient to cover the creditors' debt. The problems faced in writing this thesis are what the legal consequences are and what legal remedies for creditors if the bankruptcy bill is insufficient. The research method used in writing this thesis is normative legal research. The results show that the legal consequences and legal remedies for creditors if the bankruptcy bill is insufficient, of course the creditors have the right to receive their debt repayment from the debtor in accordance with the total bill and the payment method specified in the agreement. The management of the assets of the bankrupt debtor is transferred to a curator who is supervised by the supervisory judge, so that all actions affecting the bankruptcy assets, whether detrimental or profitable, must be carried out with the approval of the curator. Whereas legal remedies for creditors if the bankruptcy bill is insufficient, of course in this case refers to the decision to withdraw the bankruptcy statement, bankruptcy law through Article 19 paragraph (2) opens legal remedies for parties who are not satisfied with the decision by filing an appeal and / or Reconsideration to the Supreme Court.